Complete mitochondrial genomes of the critically endangered Ship sturgeon Acipenser nudiventris from two seas - Mugue, Nikolai (Mitochondrial DNA B Resour, 2016)
Two complete mitochondrial genome sequences of ship sturgeon Acipenser nudiventris from the Caspian Sea and from Balkhash Lake (introduced from the Aral Sea during the last century) were determined by PCR-based sequencing method. The whole mitogenome sequences have been deposited in GenBank under accession numbers KU321568 and KU321569.